Brain-computer interface clinical trial design considerations and clinical outcome assessments in pivotal studies: a summary of the 11th BCI society meeting 2025 workshop - Abbey Sawyer; Cristin G Welle; Jennifer French; Jessica Kelemen; Luke Bashford; Daniel R Kramer; David McMullen; Robert Franklin; Matthew R Angle; Dustin Herrmann; Thomas Oxley; Jacqueline Dister; et al. (Journal of Neural Engineering, 2026)
Abstract Objective: The Brain Computer Interface (BCI) Society Meeting 2025 held a workshop in collaboration with the Implantable BCI Collaborative Community (iBCI-CC) to discuss the selection, development and validation of clinical trial outcome assessments (COAs) for pivotal studies of BCIs. The iBCI-CC Clinical Study Endpoints Workgroup aims to build consensus on a COA framework that can meet the demands of emerging iBCI trials.
Approach: The workshop brought together diverse stakeholders from the iBCI-CC community and beyond, including industry, academic and government institutions to engage in pre-competitive collaborative discussion.
Main results: Through presentations, panel discussions and breakout groups, workshop participants highlighted meaningful aspects of health (MAHs) relevant to iBCI users, clarified the need to define corresponding concepts of interest (COIs) and to identify or adapt clinical outcome assessments (COAs) capable of capturing both functional impact and real-world use. Key challenges highlighted during the workshop are patient heterogeneity, the lack of widely validated and fit-for-purpose COAs, and the need to capture meaningful outcomes in home and daily-life environments. Lessons drawn from trials such as ADAPT-PD underscore the value of capturing device performance in home and daily-life settings, highlighting the need for context-sensitive and flexible metrics that reflect patient priorities.
Significance: This workshop lays a foundation for the iBCI-CC Clinical Study Endpoints Workgroup to establish a transparent process for identifying MAHs and COIs that are suitable for specific iBCI technologies, patient-informed, and conducive to regulatory approval and reimbursement. By combining rigorous, quantitative assessment with patient-informed goals, iBCI clinical trials can advance toward safe, effective, and accessible neurotechnologies that enhance how a person with a severe motor impairment feels, functions and survives.